2018
DOI: 10.1016/j.chiabu.2018.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Understanding trends in neighborhood child maltreatment rates: A three-wave panel study 1990–2010

Abstract: This study examines how changes in the social and economic structure of neighborhoods relate to changes in child maltreatment report rates over an extended period. The panel study design allows us to partition the changes in child maltreatment report rates into a portion associated with how the levels of socio-economic risk factors have changed over time, and a portion related to how the relative importance of those factors in explaining maltreatment report rates has changed over time. Through the application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 55 publications
2
40
0
Order By: Relevance
“…At the community and systems levels, protective factors are often tied to neighborhood socioeconomic status (SES). With child maltreatment rates, neighborhood effects have been consistently reported (Coulton et al 2018), with low neighborhood SES being associated with higher levels of abusive head trauma (AHT) and neglect (Coulton et al 2018). Indeed, in many countries, health and injury-related outcomes proportionately improve as people’s social status increases (Orpana and Lemyre 2004).…”
Section: Various Approaches To Protective Factorsmentioning
confidence: 99%
“…At the community and systems levels, protective factors are often tied to neighborhood socioeconomic status (SES). With child maltreatment rates, neighborhood effects have been consistently reported (Coulton et al 2018), with low neighborhood SES being associated with higher levels of abusive head trauma (AHT) and neglect (Coulton et al 2018). Indeed, in many countries, health and injury-related outcomes proportionately improve as people’s social status increases (Orpana and Lemyre 2004).…”
Section: Various Approaches To Protective Factorsmentioning
confidence: 99%
“…Yet, our current mixed system of universal and professional reporting and mandatory services has not decreased child maltreatment deaths (Palusci and Vandervort 2014;U.S. DHHS 2018) and contradicts knowledge that higher levels of community involvement and organization are associated with lower levels of aggression and violence (Coulton et al 2018), and a more positive perception of community social control is associated with lower levels of physical assault (Kim and Maguire-Jack 2015). Community -and perception of community -changes the relationship between parents and children.…”
Section: Introductionmentioning
confidence: 98%
“…1 Further, our understanding of the epidemiology of child maltreatment has increased in the years since the development of our current child welfare system. We now know that maltreatment results from a complex array of stressors, such as poverty and material hardship (e.g., Cancian et al 2013;Maguire-Jack and Font 2017;Pelton 2015;Slack et al 2017;Warren and Font 2015;Yang 2015;Yang and Maguire-Jack 2016), neighborhood disadvantage (Coulton et al 2018;Drake and Pandey 1996;Freisthler 2004;Maguire-Jack and Font 2017;McLeigh et al 2018), lack of social support (e.g., Freisthler et al 2014;Thompson 1995Thompson , 2015Turner and Avison 1985) and community cohesion (e.g., Barnhart and Maguire-Jack 2016;Emery et al 2015;Garbarino and Kostelny 1992; Kim and Maguire-Jack 2015; Maguire-Jack and Showalter 2016; Maguire-Jack and Wang 2016; Molnar et al 2016;Weissbourd and Grimm 1981;Zolotor and Runyan 2006), the built environment (Haas et al 2018;McDonell and Skosireva 2009) and changing family dynamics (e.g., Melton et al 2002). Indeed, mounting research evidence from as early as the 1980s has suggested that comprehensive child maltreatment prevention efforts need to address communitylevel structures and processes (e.g., Barry 1994;Belsky 1980;Garbarino and Kostelny 1992;Garbarino and Sherman 1980;Melton 1992; National Commission on Children 1991; Schorr 1988).…”
Section: Introductionmentioning
confidence: 99%